Variations in straw fodder quality and grain–straw relationships in a mapping population of 287 diverse spring wheat lines - Joshi, Arun Kumar; Kumar, Uttam; Mishra, V.K.; Chand, Ramesh; Chatrath, R.; Naik, Rudra; Biradar, Suma S.; Singh, Ravi P.; Budhlakoti, Neeraj; Devulapalli, Ravi; Blümmel, Michael (Elsevier, 2019)
A wheat association mapping population consisting of 287 diverse spring wheat lines were evaluated for three years in one location (Varanasi) and out of these for one year across three locations (Karnal, Dharwad and Varanasi) in India. Straw fodder quality traits analyzed were nitrogen (N) content, neutral (NDF) and acid (ADF) detergent fiber, acid detergent lignin (ADL), ash (ASH), in vitro organic matter digestibility (IVOMD) and metabolizable energy (ME) content. Grain yield (GY) and straw yield (SY) were also recorded. Highly significant (P < 0.0001) differences among lines were observed for all traits except for ADF and ADL in the three years trials conducted at Varanasi. However, year and location had strong (P < 0.0001) effects on all traits. Compared to line-dependent variations in GY and SY variation in straw fodder quality traits were small. Proportionally greatest variations between lines were observed for straw N where lowest and highest N varied by about 30%. Difference for NDF and ADF between lines were at most 4% units and below 3% units for IVOMD. Grain yield and straw yield were positively correlated (P < 0.0001) with GY accounting for 26% of the variation in SY. Straw N, IVOMD and ME were weakly but significantly (P < 0.05) negatively associated with GY and SY. Straw NDF and ADF were significantly (P < 0.05) positively correlated with GY but the association was again weak. Straw NDF, ADF and ADL were also weakly but significantly positively correlated with SY. Genome-wide association studies (GWAS) were applied to detect significant marker- straw fodder quality trait associations. Five genomic regions contributed for six traits (ADF, ADL, ASH, IVOMD, ME and NDF). ADF and ADL mapped in the common QTL region on chromosome 2B. Similarly, for the IVOMD and ME QTLs on chromosome 5B were associated with SNP marker, wsnp_Ku_c35090_44349517. While some associations were detected for ADF, ALD, ASH, IVOMD, ME and NDF on chromosomes 1A, 2B, 3A, 5A and 5B, the phenotypic variation explained was low to medium by individual QTL. A likely contributing factor was the comparatively small difference in straw fodder quality traits among the lines. It is interesting to note that line dependent variations in GY and SY were about two-fold. In other words, strong genotypic variations of GY and SY do exist. The lack of any similar variations in straw fodder quality traits is intriguing and requires further research.